Exploring the linkages between poverty, marine protected area management, and the use of destructive fishing gear in Tanzania - Silva, Patricia, 1973- 1973- (Policy research working paper, 2006)
"Coastal resources in Tanzania have come under increasing pressure over the past three decades, which has led to a significant decline in the biodiversity and productivity of coastal ecosystems. The livelihoods of coastal communities that directly depend on these resources are consequently under increasing threat and vulnerability. Marine protected areas (MPAs) are one tool for managing coastal and marine resources that have been increasingly used in Tanzania. Promotion of alternative income generating activities (AIGAs) is often a component of MPA management strategies to reduce fishing pressure and address poverty concerns. However, empirical evidence on whether these AIGAs are successful in reducing pressure on fisheries, or their impact on poverty, is scarce and inconclusive. This paper seeks to contribute to this debate by investigating the linkages between household characteristics, MPA activities, and household choice of fishing gear. The empirical analysis is based on household survey data from a sample of villages located along the coast of mainland Tanzania and Zanzibar. The author finds that some aspects of poverty increase the likelihood of using destructive fishing gear. MPAs do not directly affect household choice of fishing gear. However, households participating in AIGAs are less likely to use destructive fishing gear, suggesting that MPA support to these activities in Tanzania has a positive influence on household choice of fishing gear. The author also finds the use of destructive fishing gear is associated with higher consumption levels, whereas participation in AIGAs does not significantly affect household consumption levels. "--World Bank web site